Comparative genome-wide analysis of Ovis aries in Saudi Arabia highlighting inbreeding and genetic isolation of the Najdi sheep breed - Aldawish, Abdulrahman K.; Ibrahim, Mohanad A.; Alsubaie, Faisal M.; Saquib, Quaiser; Albeshr, Mohammed Fahad (Frontiers in Genetics, 2025)
IntroductionSheep (Ovis aries) farming through traditional practices plays a vital role in the socio-economic development of the Kingdom of Saudi Arabia (KSA). Genetic relationships among KSA sheep breeds remain poorly characterized.MethodsIn this study, we performed a comparative genome-wide single-nucleotide polymorphism (SNP) analysis of three sheep breeds (Najdi, Naemi, and Harri) to evaluate their genetic diversity. Blood samples from 95 individuals were genotyped using OvineSNP50 BeadChip, generating 34,026 high-quality SNPs.Result and discussionMinor allele frequency (MAF) distribution revealed the highest genetic diversity in Naemi, followed by Harri and Najdi. The run of homozygosity (ROH)-based inbreeding coefficient (FROH) identified Najdi as the most inbred (FROH = 0.053), indicating its historical isolation, while Naemi displayed minimal recent inbreeding (FROH = 0.003). The heterozygosity-based inbreeding coefficient (FIS) was highest for Najdi (FIS = 0.092), followed by Harri (FIS = 0.027), indicating a greater level of inbreeding, while Naemi (FIS = −0.055) showed signs of outbreeding.ConclusionPrincipal component (PC) and admixture analyses distinctly separated Najdi from the other two breeds, reflecting its unique genetic identity. Wright’s fixation index (FST) further affirmed genetic differentiation between Najdi and Naemi. Moreover, 336 high-FST SNPs were identified, which were linked to breed-specific genetic signatures. Our study reveals genetic diversity among local breeds and highlights the need for conservation efforts for the Najdi sheep.